2018
DOI: 10.1002/pds.4679
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol dispensing patterns and trends in Canada, 2007‐2016

Abstract: Purpose Opioid use and associated mortality and morbidity have substantially increased in Canada, which recent interventions have aimed to reduce. Tramadol is an atypical prescription‐only (but unscheduled under Canada's narcotics law) opioid analgesic and not subject to controls for other (eg, strong) opioids. Given experiences in different jurisdictions, tramadol may have been increasingly dispensed as a “substitute” drug during a period with increasingly restrictive controls for other (scheduled) opioids. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Tramadol, a commonly used weak opioid for the treatment of pain, has been considered an analgesic alternative, since its perceived risk of serious cardiovascular and gastrointestinal adverse effects was lower than that of nonsteroidal anti‐inflammatory drugs (NSAIDs), and its risk of addiction and respiratory depression was lower than that of traditional opioids . As a result, tramadol use has been increasing rapidly worldwide over the past decades .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tramadol, a commonly used weak opioid for the treatment of pain, has been considered an analgesic alternative, since its perceived risk of serious cardiovascular and gastrointestinal adverse effects was lower than that of nonsteroidal anti‐inflammatory drugs (NSAIDs), and its risk of addiction and respiratory depression was lower than that of traditional opioids . As a result, tramadol use has been increasing rapidly worldwide over the past decades .…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol, a commonly used weak opioid for the treatment of pain, has been considered an analgesic alternative, since its perceived risk of serious cardiovascular and gastrointestinal adverse effects was lower than that of nonsteroidal anti‐inflammatory drugs (NSAIDs), and its risk of addiction and respiratory depression was lower than that of traditional opioids . As a result, tramadol use has been increasing rapidly worldwide over the past decades . For example, data from Truven Health Analytics MarketScan in the United States showed that prescriptions of tramadol increased by 22.8% between 2012 and 2015, and tramadol dispensing rates increased in each of the provinces in Canada, with the highest in Nova Scotia increasing from 0.50/defined daily doses (DDD) in 2007 to 2.64/DDD in 2016 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, tramadol is not classified as a scheduled drug in Korea, unlike opioids, ; thus, tramadol is widely used instead of opioids. In a similar case, a recent study in Canada showed that tramadol (unscheduled under Canada's narcotics law) use is considerable (although it is not considered a substitute for strong opioids) as an alternative intervention for reducing opioid use . In Korea, duplicate use of tramadol has been confirmed under a nationwide drug utilization review system; however, duplicate use is possible by entering a specific reason for duplication in the system because it is not mandatory to change the prescription to avoid duplicate use .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar case, a recent study in Canada showed that tramadol (unscheduled under Canada's narcotics law) use is considerable (although it is not considered a F I G U R E 2 Age-and sex-standardized prevalence of tramadol use at least once a year, and age-standardized prevalence of using tramadol twice or more a year in 2014-2016 substitute for strong opioids) as an alternative intervention for reducing opioid use. 29 In Korea, duplicate use of tramadol has been confirmed under a nationwide drug utilization review system; however, duplicate use is possible by entering a specific reason for duplication in the system because it is not mandatory to change the prescription to avoid duplicate use. 30 The reasoning for this behaviour has been postulated as a lack of understanding of opioid prescriptions for non-cancer pain by healthcare providers.…”
Section: Discussionmentioning
confidence: 99%